Sintesis dan Karakterisasi Fotokatalis TiO2/Cu Menggunakan Lampu UV - Syawal, M Ichlas; Suryani, Okta (Lembaga Yasin AlSys, 2023)
Most of the energy consumed comes from non-renewable fossil fuel resources. Burning fossil fuels has been found to be a major cause of environmental pollution and greenhouse gas emissions, making it the most common energy source. Therefore, renewable and environmentally friendly energy resources are needed, namely sunlight. One way to utilize sunlight is to store it into hydrogen compounds. Hydrogen comes from water through a process of breaking down its molecules which is called water decomposition. Water decomposition uses sunlight and a semiconductor photocatalyst, such as TiO2. In this research, TiO2 doped with Cu metal has been synthesized using UV lamp irradiation. TiO2 has been successfully synthesized. XRD characterization to determine the structure of TiO2. TiO2 has an anatase crystal structure. Then XRF characterization is done to see the percentage of Cu that has been successfully doped. When exposed to a UV lamp for 1 hour, 0.347% Cu was successfully doped. When exposed to a UV lamp for 5 hours, 1.28% Cu was successfully doped.